Tax literacy among individual taxpayers - Ismail, Hashanah; Minai, Badriyah; Muhamed, Salmah (Taiwan Institute of Business Administration, 2011)
This paper reports on a survey of tax literacy level of 200 individual taxpayers. Using the Eriksen and Fallen (1996) model of knowledge index to measure the taxpayers’ tax knowledge, the study finds that gender, use of e-filing and ethnicity are factors significantly related to tax literacy.